Psychological Alienation and Substance Use among Adolescent Abusers at Psychiatric Teaching Hospitals in Baghdad - Mahdi, Noor S.; Mohammed , Qahtan Q. (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: The present study aims at assessing the level of psychological alienation as phenomenon among adolescent substance abusers; determining the relationship between psychological alienation and substance use.Methods: A descriptive correlational design used in the present study was established for the period from October 10th, 2019 to march 20th, 2020. The study was conducted on a non- probability (convenient) sample of 60 adolescents with substance use disorder which were selected from the inpatient psychiatric teaching Hospitals. The instrument of the study is adopted and modified for the purpose of this study. Psychological alienation scale was used in this study, this scale contain 50 items taken from Denial Abbas study (2016). The data were analyzed through the application of descriptive and inferential statistical approaches which are applied by using IBM/SPSS package version 24.0.Results: the result of the present study showed that adolescent abusers were age group (21 ≤ years) (55%), and with primary level of education (43.3%), and with unmarried (61.7%), and (80%) of them living in low class neighborhood. 76.7% of them are work, with sufficient monthly income (36.7%), and used drugs was (51.7%), and they were substances abuser for one to five years (70%), bad friends was cause of substance abuse (50%). The substance abusers are experiencing a moderate level of psychological alienation as presented in findings that (65%). There are no correlation between psychological alienation and substance use.Conclusions: the study concluded that Psychological alienation does not related to substance use addiction as concluded by insignificant correlation between substance use and psychological alienation. The severity of psychological alienation is influenced by the causes of substance uses among those addicted client.Recommendations: the study recommended conducting more studies on the phenomenon of psychological alienation and its relationship to drug use and its effects on adolescents and linking it to new changes, and the study also recommended building treatment counseling programs to deal with the problem of drug abuse and its spread among adolescents and setting the appropriate treatment for its psychological effects.